Fatigue crack propagation in welded joints X70 - Adel Deliou; Benattou Bouchouicha (Fracture and Structural Integrity)
Structural failure assessment approaches take into account local parameters, specimen geometry, loading and material. In the case of welded joints, in addition to these parameters, consideration must be given to the effect of the heterogeneity of properties due to welding. The objective of our work is to study the fatigue crack propagation of welded joint in API X70 pipeline steel. This experimental study focused on welded joints in the different parts, base metal, weld metal and heat affected zone. The concepts of fracture mechanics are used to analyze the harmfulness of defects in welded joints and the main part of fatigue life falls on the crack propagation. The results obtained show that the fatigue crack propagation rate of cracks in the heat affected zone is delayed compared to the other zones. The effect of the microstructure and the quality of submerged arc welding of the studied X70 steel are significant. Tensile tests, hardness and measurement of energetically parameters complemented this work.